2021
DOI: 10.1093/nutrit/nuab039
|View full text |Cite
|
Sign up to set email alerts
|

Gluten-free diet can ameliorate the symptoms of non-celiac autoimmune diseases

Abstract: Context A gluten-free diet (GFD) is the recommended treatment for gluten-dependent disease. In addition, gluten withdrawal is popular and occasionally is suggested as a treatment for other autoimmune diseases (ADs). Objective The current systematic review summarizes those entities and discusses the logic behind using a GFD in classical non–gluten-dependentADs. Data Sources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 123 publications
0
9
0
Order By: Relevance
“…(20) Conversely, large intakes of compounds found in processed foods such as sugar and gluten is associated with gut dysbiosis, systemic inflammation and exacerbation of SLE symptoms. (4,7,21,22) Petric et al found that SLE patients in clinical remission who often ate meat, fast food or fried foods had lower levels of C3 than patients who had high intake of vegetables, fruit and fish. (12) Interestingly, substituting a serving of red meat with alternative protein sources (including poultry, fish, legumes or nuts) has been associated with lower CRP levels.…”
Section: Discussionmentioning
confidence: 99%
“…(20) Conversely, large intakes of compounds found in processed foods such as sugar and gluten is associated with gut dysbiosis, systemic inflammation and exacerbation of SLE symptoms. (4,7,21,22) Petric et al found that SLE patients in clinical remission who often ate meat, fast food or fried foods had lower levels of C3 than patients who had high intake of vegetables, fruit and fish. (12) Interestingly, substituting a serving of red meat with alternative protein sources (including poultry, fish, legumes or nuts) has been associated with lower CRP levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, this observation does not answer the question of whether GFD may be effective in T1D patients without CD. The hypothesis that gluten is harmful not only to patients with CD but also to those with other autoimmune diseases was suggested recently [ 33 , 35 ]. Researchers suggest that GFD may offer the potential to reduce the risk of T1D [ 36 ], and a few studies indicate that GFD, when applied to older children with T1D, may protect beta cells from destruction to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Those three interrelated pathways are the basis for our current novel hypothesis, whereby, two very common environmental domains, plants and microbes, and gluten and mTG, respectively, are joining together to induce autoimmunity and other gluten-dependent inflammatory diseases 4 , 7 , 9 , 22 , 26 , 27 , 32 , 39 , 41 . Interestingly, gluten avoidance was recently reported to alleviate symptoms and disease activity of non-celiac ADs 81 , 82 , 102 – 106 , although, gluten withdrawal is not devoid of side effects 107 109 . Taken together, both external factors, the mTG and gluten-containing nutrients, can operate as the mythological Trojan horse to drive luminal and extra-intestinal ADs 29 .…”
Section: Discussionmentioning
confidence: 99%